Efficient Colorimetric Fluoride Anion Sensor Based on π-Conjugated Carbazole Small Molecule - Deng, Zhifeng; Wang, Cheng; Li, Junqiang; Zheng, Meng (Frontiers in Chemistry, 2021)
The ability to detect fluoride anions with high selectivity and sensitivity by using the naked eye is crucial yet challenging. In this study, a novel, simple conjugated organic dye, N-tert-butyldimethylsilyl-3,6-diiodocarbazole (CA-TBMDS) was developed and used for the first time as a colorimetric sensor for fluoride. CA-TBMDS was found to be a highly sensitive fluoride chemosensor, with a detection limit as low as 3 × 10−5 M. The reaction of CA-TBMDS with fluoride anions in a tetrahydrofuran solution resulted in a color change from colorless to yellow under ambient light, which can be discriminated by the naked eye. The sensor operated via intermolecular proton transfer between the amide units and the fluoride anion, as confirmed by proton nuclear magnetic resonance titration. CA-TBMDS is not only highly sensitive to fluoride anions, but also exhibits high sensitivity in the presence of various ions. This work demonstrates that N-butyldimethylchlorosilane-based organic dyes have prospective utility as a type of fluoride anion chemosensor.